2020
DOI: 10.1093/ehjci/jeaa276
|View full text |Cite
|
Sign up to set email alerts
|

External elastic lamina vs. luminal diameter measurement for determining stent diameter by optical coherence tomography: an ILUMIEN III substudy

Abstract: Aims Optical coherence tomography (OCT)-guided external elastic lamina (EEL)-based stent sizing is safe and as effective as intravascular ultrasound in achieving post-procedural lumen dimensions. However, when compared with automated lumen diameter (LD) measurements, this approach is time-consuming. We aimed to compare vessel diameter measurements and stent diameter selection using either of these approaches and examined whether applying a correction factor to automated LD measurements could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…A step-by-step guide for measurement of vessel diameter and selection of stent diameter is provided in Figure 3. Briefly, an EEL-guided device sizing strategy is preferable to a lumen-guided strategy as it leads to the selection of a larger device size (≈0.5 mm) and consequently a larger lumen area without an increase in postprocedural complications [20][21][22] . EEL measurements may be utilised if two separate diameter measurements can be made in two different locations in the arterial wall that are at least one quadrant of the arterial circumference apart from each other.…”
Section: Pre-pci Guidance Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…A step-by-step guide for measurement of vessel diameter and selection of stent diameter is provided in Figure 3. Briefly, an EEL-guided device sizing strategy is preferable to a lumen-guided strategy as it leads to the selection of a larger device size (≈0.5 mm) and consequently a larger lumen area without an increase in postprocedural complications [20][21][22] . EEL measurements may be utilised if two separate diameter measurements can be made in two different locations in the arterial wall that are at least one quadrant of the arterial circumference apart from each other.…”
Section: Pre-pci Guidance Morphologymentioning
confidence: 99%
“…If EEL visualisation is insufficient, the mean lumen diameter, recorded from the automated lumen profile feature, is utilised for device sizing. Lumen-based measurements should be rounded up, between 0.25 and 0.5 mm, to determine the device size 20 . The distal measurements determine the stent size and post-dilation balloon size at the distal segment of the stent, and the proximal measurements determine the balloon size for post-dilation at the proximal segment of the stent.…”
Section: Pre-pci Guidance Morphologymentioning
confidence: 99%
“…ILUMIEN III trial showed the lower percentage of malapposition in OCT-guided PCI with EEL-based approach than in angiography-guided PCI [ 8 ]. The sub-analysis of the trial also revealed that EEL-based approach led to selection of larger stent diameter than lumen-based approach [ 28 ]. Moreover, the sub-analysis of MECHANISM study revealed that EEL-based approach was safe and feasible as compared to lumen-based approach in stable coronary artery disease [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…A major advantage of IVUS stems from its relatively deep tissue penetration (5–6 mm) [ 1 ] ( Table 1 ). This allows full-thickness visualization of the vessel wall, enabling the usage of vessel size parameters, such as the external elastic membrane (EEM) diameter or reference lumen diameters for stent sizing [ 16 ], which plays a significant role in PCI optimization, as overestimation or underestimation of stent size may instigate complications such as coronary dissection, perforation, extensive malapposition or stent underexpansion [ 17 ]. Additionally, visualizing all layers of the vessel wall can be useful in follow-up assessment, being able to show vessel remodeling processes [ 18 ] or providing detailed imaging when angiography suggests late acquired stent malapposition (persistent staining or aneurysmal change) [ 1 ].…”
Section: Advantages and Disadvantages Of Ivus Imagingmentioning
confidence: 99%